PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN MEDIA GAMBAR SERI DI KELAS IV SEKOLAH DASAR - lisda, setri wulandari; fitria, yanti; sukma, elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the improvement of narrative essay writing skills using series drawing media in grade IV elementary school students. The type of research is PTK using qualitative and quantitative approaches. This research was conducted at SDN 52 Parupuak Tabiang, Padang City with a total of 25 students consisting of 7 male students and 18 female students. The average value of students' narrative essay writing skills in the pre-writing stage in the first cycle of 75.5 increased in the second cycle 82, the writing stage in the first cycle 51.33 increased in the second cycle 74.7, the post-writing phase of the first cycle 79.7 increased in the cycle II 88Keywords: Writing, Narrative text, Series Image Media